Effects of different heel heights on selected gait parameters of young undergraduate females - Nwankwo, Maduabuchi Joseph; Egwuonwu, Afamefuna Victor; Ezeukwu, Antoninus Obinna; Nwafulume, Chidubem Kamdilichukwu (Archives of Advances in Biosciences, 2012)
The objective of this study was to determine the effects of different heel heights on selected gait parameters in a sample of young Nigerian females. A purposive sample of eighty apparently healthy undergraduates of Nnamdi Azikiwe University, Nnewi Campus participated in the study. Their mean age, height, and weight were 21.98± 1.83 years, 1.65±0.06 meters, 59.50±9.34 kilograms respectively. An ex post facto design was used to investigate the effect of different heel heights (3.2cm, 7.8cm and 11.0cm) on selected gait parameters. This was done using a prepared protocol and measurement of gait parameters were taken with a tape rule and stop watch respectively. One-way ANOVA was used to compare differences across the groups. Level of significance was set at 0.05. There were significant differences in mean values of selected gait parameters across the different heel heights for stride length, step length, stride width, cadence, and velocity respectively. However, with post hoc test, no significant difference exist in mean values between bare foot and low heel of all selected parameters for stride length, step length, and cadence respectively, barefoot and mid heel (p=0.142), and mid and high heel for stride width (p= 0.162) respectively. There was a significant difference exists only between low and high heel on velocity. As heel height increases, gait parameters such as stride length and step length shorten while the cadence increases and the stride width widens. It is recommended that to maintain comfort and reduce the adverse side effects associated with wearing the different heel height, women are advised to minimize putting on heeled shoes particularly the mid and high heels.